Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I would like to apply Legendre polynomials to least square approximation. Therefore I would like the function:

$$L_n (x)=\sum_{k=0}^n a_k P_k (x)$$

to fit $f(x)$ defined over $[-1,1]$ in a least square sense.

We should minimize:

$$I(a_0, ..., a_n)= \int_{-1}^1 [f(x) - L_n (x)]^2 \; dx\tag1$$

and so we must set

$$\frac{\partial I}{\partial a_r} = 0,\qquad r=0,1, \ldots,n\tag2$$

Using equations $(1)$ and $(2)$

$$\int_{-1}^1 P_r(x) \left[f(x) - \sum_{k=0}^n a_k P_k (x)\right]dx = 0,\qquad r=0,1, \ldots,n$$

should be an equivalent term.

My question now is: why is that true?

I would be glad if someone could illustrate the last step with more details. Thanks, Rainier.

share|cite|improve this question
thx for editing, looks much nicer now. – rainier Sep 15 '12 at 15:58
It is true because the functional $I(a_0\ldots a_n)$ that you want to minimize is convex. Hence any critical point is a minimum. – Giuseppe Negro Sep 15 '12 at 16:10
ok, equation (1) and (2) make perfect sense to me. The step which I don't understand is how to get to the last term. – rainier Sep 15 '12 at 16:32

You have

$$ \frac{\partial}{\partial a_r}\int_{-1}^1 [f(x) - L_n (x)]^2dx=0\\ \int_{-1}^1 \frac{\partial}{\partial a_r}[f(x) - L_n (x)]^2dx=0\\ \int_{-1}^1 2[f(x) - L_n (x)]\frac{\partial}{\partial a_r}[f(x) - L_n (x)]dx=0\\ \int_{-1}^1 2[f(x) - L_n (x)][0 - \frac{\partial}{\partial a_r}L_n (x)]dx=0\\ -\int_{-1}^1 2[f(x) - L_n (x)]\frac{\partial}{\partial a_r}\sum a_kP_k(x)dx=0\\ -\int_{-1}^1 2[f(x) - L_n (x)]P_r(x)dx=0 $$

share|cite|improve this answer

It is even easier than that. Because the Legendre polynomials are orthogonal, you can get the coefficients just from $a_n=\frac {2n+1}2\int_{-1}^1f(x)P_n(x)dx$

share|cite|improve this answer

This is coming late but for the benefit of others, let me post my opinion:

$$\frac{\partial\sum_{k=0}^n a_k P_k (x)}{\partial a_r} = \frac{\partial}{\partial a_r} [a_0 P_0 + a_1 P_1 + ... + a_r P_r + ... + a_k P_k] = P_r (x)$$

This is because all other coefficients of $$P_k (x) $$ are treated as constants except for when $$k=r$$

The Orthogonality of the Legendre Polynomial was what was responsible for the final step

$$\int_{-1}^1 P_r(x)P_k (x)dx = 0, \qquad r=0,1, \ldots,n$$

The above equation is true as long as r is not equal to k

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.